2015
DOI: 10.1152/jn.00450.2015
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanisms through which spatial attention acts on nociception

Abstract: showing that spatial attention is further able to modify the chronometry of nociceptive processing by modulating the latency and temporal jitter of the recorded responses. The mechanisms through which attention could possibly modulate nociceptive processing are discussed here, with a particular focus on novel findings and future perspectives.laser-evoked potentials; spatial attention; nociception PAIN IS A COMPLEX EXPERIENCE that emerges, in normal conditions, in response to the activation of peripheral nocice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Furthermore, previous studies have also shown that spatial attention can increase the magnitude of the negative vertex component elicited by stimuli belonging to several modalities (e.g. [9,10,20,41], see [3,12,21,34] for reviews and commentary). Therefore, a possible explanation to the "crossmodal sensitization" observed in the present study could be that HFS-related sensations induce cross-modal links in endogenous or exogenous spatial attention.…”
Section: Short-vs Long-lasting Effects Of Hfsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, previous studies have also shown that spatial attention can increase the magnitude of the negative vertex component elicited by stimuli belonging to several modalities (e.g. [9,10,20,41], see [3,12,21,34] for reviews and commentary). Therefore, a possible explanation to the "crossmodal sensitization" observed in the present study could be that HFS-related sensations induce cross-modal links in endogenous or exogenous spatial attention.…”
Section: Short-vs Long-lasting Effects Of Hfsmentioning
confidence: 97%
“…Twenty-six participants took part in the experiment (18 women, 8 men, median age 23, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Participants were recruited among students and staff of the university and were naïve to the aims of the study.…”
Section: Participantsmentioning
confidence: 99%